METHODOLOGY FOR WHITE STORK MONITORING THROUGH INTEGRATION OF REMOTE SENSING AND FIELD RESEARCH (Universal International Scientific Journal, 2026)
This article develops and tests a methodology for integrating remote sensing and field surveys to monitor the population of the white stork — Ciconia ciconia asiatica in the Fergana Valley. As a result of the research conducted in 2021–2023, nests were identified and verified in the field using Google Earth satellite imagery, NDWI (Normalized Water Index) analysis, and vehicle transects. As a result, a total of 897 nests were recorded, of which 834 (93%) were occupied by breeding pairs. The area of ​​potential habitats identified based on NDWI was 11,511.5 km², and 82% of the data were in agreement with field data. The results of the study showed that high accuracy and efficiency can be achieved when remote sensing methods are combined with field observations. The developed methodology allows for monitoring the white stork on a republic-wide basis based on a single standard.
Keywords: White Stork; remote sensing; NDWI